Artificial Societies and Social Simulation Using Ant Colony, Particle Swarm Optimization and Cultural Algorithms - Ochoa, Alberto; Hernández, Arturo; Cruz, Laura; Ponce, Julio; Montes, Fernando; Li, Liang; Janacek, Lenka (IntechOpen, 2010)
None